Differences in executive functions applied to memory processes in people with migraine: a cross-sectional study - Quiroz Padilla, Maria Fernanda (2017)
The aim of this cross-sectional study was to identify differences in memory processes and the role of executive functions in memory, in people with migraine and in a control group. Neuropsychological evaluation was made in one session on 63 participants distributed into interictal migraine-with-aura (n = 24), interictal migraine-without-aura (n = 16) and control (n = 23) groups. ANOVAs on the individual tasks revealed statistically significant differences between groups on Rey-Osterrieth direct and percentile copy strategy and recall (both p < 0.001). Differences were identified between control and migraine groups in performance on the Rey-Osterrieth Complex Figure, but not on other memory tasks, suggesting the existence of brain dysfunctions in people with migraine affecting organizational and planning abilities that are necessary for visual memory.